Premonitory Urges and Sensorimotor Processing in Tourette Syndrome - Sangeerthana Rajagopal; Stefano Seri; Andrea Eugenio Cavanna (Behavioural Neurology)
Most patients with Tourette syndrome report characteristic sensory experiences (premonitory urges) associated with the expression of tic symptoms. Despite the central role of these experiences to the clinical phenomenology of Tourette syndrome, little is known about their underlying brain processes. In the present article we present the results of a systematic literature review of the published studies addressing the pathophysiological mechanisms of premonitory urges. We identified some preliminary evidence for specific alterations in sensorimotor processing at both cortical and subcortical levels. A better insight into the brain correlates of premonitory urges could lead to the identification of new targets to treat the sensory initiators of tics in patients with Tourette syndrome.